KONSEPSI LOKAL-GLOBAL SEBAGAI BASIS KULTURAL BERKESENIAN SANGGAR DEWATA INDONESIA - I Gede Arya Sucitra; Sartini Sartini (Fakultas Sastra Universitas Negeri Malang, 2020)
GLOBAL-LOCAL CONCEPT AS A CULTURAL BASIS FOR ART IN SANGGAR DEWATA INDONESIAAbstract: The face of Indonesian art contains multicultural, intercultural, and diverse values in the dialectics of regional arts and global culture. The rise of local culture is often caused by global cultural friction. The attraction and tension between global culture and local culture results in the 'glocalization' of culture. This article aims to explore the values of locality and global culture as a creative foundation for art in the Balinese diaspora art community, Sanggar Dewata Indonesia (SDI) which is culturally and philosophically insightful. The Balinese diaspora gradually has a new cultural identity as a result of the acculturation of Balinese culture with the local culture. Likewise, in the aspect of the language of art, Balinese diaspora artists in Yogyakarta are accommodative, experiencing visual transformation, syncretic, and contain hybridization of cultural values. This study utilizes qualitative methods with a formal study of cultural philosophy through an interpretive approach. The cultural interpretive approach has resulted that the culture and art process of the SDI art community are symbolically the result of the legacy of the collective conception system both in communicating, perpetuating and developing knowledge to attitudes towards artistic life. The mission and vision of SDI includes the spirit of nationalism, Pancasila nationalism, multiculturalism, in order to achieve the international art world, which is more heterogeneous and competitive. Thus the local-global spirit is accompanied by a process of reinterpretation and re-contextualization of a time that presents a thinking discourse, creative vision through creative dialectics that is filled with local-global acculturation shock power towards world-class global art competition.Keywords: Globalization, Locality values, Multiculturalism, Sanggar Dewata IndonesiaKONSEPSI LOKAL-GLOBAL SEBAGAI BASIS KULTURAL BERKESENIAN SANGGAR DEWATA INDONESIAAbstrak: Wajah seni rupa Indonesia mengandung nilai multikultur, interkultural, serta berbhineka dalam dialektika kesenian daerah dan kebudayaan global. Kebangkitan kebudayaan lokal sering disebabkan oleh gesekan budaya global. Tarikan dan tegangan antara budaya global dan budaya lokal menghasilkan ‘glokalisasi’ kebudayaan. Artikel ini bertujuan mendalami nilai-nilai lokalitas dan kultur global sebagai landasan kreatif berkesenian dalam komunitas seni diaspora Bali, Sanggar Dewata Indonesia (SDI) yang berwawasan budaya serta filosofis. Diaspora Bali lambat laun memiliki identitas kultur baru hasil dari akulturasi kebudayaan Bali dengan kebudayaan lokal setempat. Demikian juga dalam aspek bahasa berkesenian seniman diaspora Bali di Yogyakarta, bersifat akomodatif, mengalami transformasi visual, sinkretis, dan mengandung hibridasi nilai-nilai budaya. Artikel ini diteliti menggunakan metode kualitatif dengan kajian formal filsafat kebudayaan melalui pendekatan interpretatif. Pendekatan interpretatif kebudayaan telah menghasilkan pembacaan bahwa kebudayaan dan proses berkesenian komunitas seni SDI secara simbolik merupakan hasil dari warisan sistem konsepsi kolektif baik dalam mengomunikasikan, mengabadikan dan mengembangkan pengetahuan hingga sikap terhadap kehidupan kesenian. Visi dan misi SDI adalah semangat kebangsaan, nasionalisme Pancasila, multikultur, demi menuju dunia kesenian internasional yang lebih heterogen dan kompetitif. Dengan demikian semangat lokal-global ini disertai proses reinterpretasi dan rekontekstualisasi zaman menghadirkan wacana pemikiran, visi kreatif melalui dialektika kreatif yang penuh daya kejut akulturasi lokal-global menuju persaingan dunia seni global.Kata kunci: Globalisasi, Nilai lokalitas, Multikulturalisme, Sanggar Dewata Indonesia Permalink/DOI: dx.doi.org/10.17977/um015v48i22020p118